Identifikasi Potensi Bahaya Pekerja Pada Proses Welding Proyek Support Frame Menggunakan Metode HIRARC di PT. XYZ - Ryan Setyo Putro Robawa; Joumil Aidil SZS (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The steel and construction industry is currently growing very rapidly due to the increasing demand from various parties who want to see the progress of infrastructure in Indonesia. Design, manufacturing, and construction are the activities of PT XYZ, a government company. The majority of initiatives are focused on the production of steel-based goods. As personnel in the fabrication and construction industry often come into direct contact with heavy machinery and materials while performing their duties, accidents and occupational diseases are hazards that are difficult to prevent. Welding is one area of work that has a high rate of accidents and occupational diseases. To ensure the welding process runs safely, this research seeks to identify potential risks and hazards that may arise and carry out risk control in each work activity. Qualitative descriptive techniques combined with risk analysis using the HIRARC method is the methodology used in this research. Based on the results of the study, overall there are fourteen possible risks, including two high categories, one medium category, and eleven extreme categories. By increasing employee awareness of occupational safety and health (OHS), PT XYZ can increase productivity without sacrificing employee welfare.